Free-Association Session Scale: factor structure and preliminary validity test - Mariani, Rachele; Di Monte, Cinzia; Caricati, Luca; Bastianini, Tiziana; Ferruta, Anna; Christopher, Christian; Speranza, Anna Maria; Guerrini degli Innocenti, Benedetta; Musetti, Alessandro (Frontiers in Psychology, 2023)
One of the main concepts of the psychoanalytic method postulated by Freud in 1912 is the fundamental rule, which involves asking the patient to say whatever comes to mind as the analyst follows the patient's speech with fluctuating attention. Despite different theoretical models, this concept has remained an invariant element that characterizes the psychoanalytic method. For this reason, the purpose of the current study is to present a new instrument that measures this process based on the clinician's assessment. The Free-Association Session Scale (FASS) has been designed according to the psychoanalytic framework. Study 1 presented the preliminary validation of the FASS factor structure. Experienced Italian psychoanalysts (N = 281; 196 women) completed the FASS and sociodemographic questionnaire. The following two factors were identified using exploratory factor analysis: (1) Perturbing, and (2) Associativity. Study 2 cross-validated the two factors using an independent sample (N = 259; 187 women) of experienced psychoanalysts and confirmatory factor analysis (CFA). The FASS has been tested for concurrent validity using the Session Evaluation Questionnaire (SEQ) and Linguistic measures of the Referential process. The two-factor model achieved a close-fit test, and the FASS items were found to measure the corresponding factors with good reliability. The Perturbing factor is negatively associated with three SEQ factors (Depth, Smoothness, and Positivity) and negatively correlated with symbolization (IWRAD and IWRAD_IWRRL), confirming a more complex and unexpected session. The Associativity factor is positively associated with all four SEQ factors (Depth, Smoothness, Positivity, and Arousal). In conclusion, the FASS is a promising new questionnaire for assessing psychoanalytic session quality processes with satisfactory validity and reliability.